Prophylactic treatments for vestibular migraine: a systematic review and network meta-analysis of randomized clinical trials - Chu, Hongyuan; Wang, Yuru; Ling, Xia; Li, Kangzhi; Yang, Xu (Frontiers in Pharmacology, 2023)
Objectives: We compared and ranked the efficacy and tolerability of multiple prophylactic treatments for vestibular migraine (VM), including β-blockers, calcium channel blockers, antiseizure medications, and antidepressants such as tricyclics and serotonin–noradrenaline reuptake inhibitors. Methods: PubMed, Web of Science, Embase, and Cochrane Center for Clinical Trials were systematically searched for relevant randomized clinical trials (RCTs) from March 2023 to May 2023. Studies on the efficacy and tolerability of prophylactic treatments for VM were included. Efficacy was measured using the average vertigo frequency per month and dizziness handicap inventory (DHI) improvement after 3–6 months of treatment. Tolerability was measured by the number of patients reporting at least one adverse event (AE). Network meta-analyses were performed according to a Bayesian framework and a random-effects model based on odds ratios or mean differences (MDs) and 95% confidence intervals (CIs). A sequence of ranking probability was calculated according to the surface under the cumulative ranking (SUCRA) curve. This network meta-analysis was previously registered with PROSPERO (CRD42023422258). Results: Five RCTs comprising 334 patients were analyzed by synthesizing the published evidence. Considering the examined prophylactic therapies, there is significant evidence that valproate acid (VPA) is superior to placebo or abortive treatment alone (MD = −4.12, 95% CI = −8.09, −0.15) in reducing the frequency of vertigo. Flunarizine (MD = 20.00, 95% CI = 10.90, 29.10), valproate acid (MD = 18.88, 95% CI = 10.42, 27.34), and venlafaxine (MD = 11.48, 95% CI = 9.84, 13.12) were significantly more effective than placebo or abortive treatment in reducing DHI. VPA most strongly reduced the frequency of vertigo according to SUCRA, but it ranked third-to-last in tolerability. Flunarizine ranked best in DHI improvement but worst in tolerability. Metoprolol ranked worst for efficacy but best for tolerability. Conclusions: VPA and flunarizine reduced the frequency of vertigo and improved DHI, but they had unfavorable tolerability. The effects of metoprolol on vertigo require further study. Given the low certainty and limited sample, additional head-to-head RCTs are warranted to further confirm efficacy.